Development of BAMSI (Busy Book for Numbers Six and Nine) as a Learning Medium for Number Recognition among Children Aged 5–6 Years - Zahara Alfina Divanti; Sri Widayati; Nurhenti Dorlina Simatupang; Afifah Rahmaningrum (Jurnal Inovasi, Evaluasi dan Pengembangan Pembelajaran, 2026)
The ability to recognize and differentiate numbers is a fundamental component of early childhood numeracy development; however, many children experience difficulties distinguishing visually similar numbers such as 6 and 9. This study aims to develop, validate, and evaluate the effectiveness of BAMSI (Busy Book for Numbers Six and Nine) as an interactive learning medium for children aged 5–6 years. The research employed a Research and Development (R&D) approach using the ADDIE model, encompassing analysis, design, development, implementation, and evaluation stages. The feasibility of the media was assessed through expert validation involving media and subject-matter experts using a Likert-scale instrument, while effectiveness was tested using a one-group pretest–posttest design with 17 kindergarten children. Assessment indicators included the ability to identify, name, and classify numbers 6 and 9. The validation results indicated that the BAMSI media was highly feasible. Furthermore, the effectiveness test showed a significant improvement in children’s number recognition abilities, as evidenced by the Wilcoxon test (p < 0.001) and an N-Gain score of 0.81 (high category). The novelty of this study lies in integrating sensorimotor-based activities that enable children to manipulate physical objects, thereby strengthening visual discrimination and conceptual understanding. These findings suggest that BAMSI is an effective, engaging, and developmentally appropriate medium for enhancing early numeracy skills.